Pengaruh Kontrol Diri Terhadap Perilaku Konsumtif Mahasiswa Pendidikan Ekonomi 2022 Universitas Lampung - Wanty Nurkholifah; Selly Ismi Safitri; Indah Nur Aulia; Rahmawati; Pujiati (STKIP Subang, 2025)
commenced their studies in 2022, tend to exhibit an increase in consumptive behaviour. This trend appears to be influenced by the ease of purchasing goods through e-commerce platforms and the continuous exposure to promotional content on social media. The objective of this study is to determine the effect of self-control on the consumptive behaviour of Economic Education students from the 2022 cohort at the University of Lampung. This research adopts a quantitative approach, employing a descriptive-verificative method. The study utilises both an ex post facto and survey-based design. Data were collected through observation, interviews, and questionnaires. The total population consisted of 104 students, from which a sample of 83 respondents was selected using the Slovin formula. The sampling technique applied was probability sampling with a simple random sampling method. The data analysis process included normality and homogeneity tests, as well as classical assumption tests comprising linearity, multicollinearity, and heteroscedasticity assessments. A simple linear regression analysis was conducted for hypothesis testing. The results indicated that the calculated t-value (tcount) = 5.988 exceeded the critical value (ttable) = 1.989, with a significance level of 0.000, which is below the 0.05 threshold. These results demonstrate that self-control has a statistically significant effect on consumptive behaviour. The coefficient of determination (R²) was 0.307, suggesting that self-control accounts for 30.7% of the variation in consumptive behaviour.